A Review on the Status and Challenges of Doctoral Programs with Special Attention to Iran - Shokrollah Assar; Mohsen Rezaeian; Gholamhossein Hassanshahi (Journal of Clinical and Diagnostic Research, 2020)
The aim of this narrative review was to consider the status and challenges of doctoral programs in the world with specific attention to Iran. In most parts of the world, everyone who is looking to pursue a doctoral degree has a special interest in research works and to expand the boundaries of knowledge. Obtaining a Doctor of Philosophy (PhD) degree, means that a person has undertaken, to develop a science along with the attempts made by other scholars in the same field. The program entails a scientific report to be prepared independently by a PhD applicant who has undertaken a research project as a part of his/her own PhD program. A PhD course/program is expected to provide a new and significant contribution in developing a narrow field of study. In some disciplines, a dissertation may develop an innovation or a new approach. To fulfill the requirements of PhD programs, PhD students are often confronted with various challenges and problems such as stress, feeling of being isolated from others, financial difficulties and lack of sufficient communication with their supervisors, not to mention potential unemployment problems that they may face in the future. The number of Iranians with a PhD degree working in the business sector is on the rise. So, this holds promise for resolving the country’s dilemmas and having only a higher degree cannot solve current problems and speeding up a better future for Iranian society.